Schaum's outline of theory and problems of differential equations - Bronson, Richard (New York McGraw-Hill, Inc., 1994)
If you want top grades and thorough understanding of differential equations, this powerful study tool is the best tutor you can have! It takes you step-by-step through the subject and gives you 563 accompanying problems with fully worked solutions. You also get plenty of practice problems to do on your own, working at your own speed. (Answers at the back show you how you're doing.)
Basic concepts -- Classifications of first-order differential equations -- Separable first-order differential equations -- Exact first-order differential equations -- Linear first-order equations -- Applications of first-order differential equations -- Linear differential equations : theory of solutions -- Second-order linear homogeneous differential equations with constant coefficents -- nth-order linear homogeneous differential equations with constant coefficients -- The method of undetermined coefficients --- Variation of parameters -- Initial-value problems -- Applications of second-order linear differential equations -- The Laplace transform -- Inverse Laplace transforms -- Convolutions and the unit step function -- Solutions of linear differential equations with constant coefficients by Laplace transforms -- Solutions of linear systems by Laplace transforms -- Matrices -- e [superscript At] -- Reduction of linear differential equations to a first-order system -- Solutions of linear differential equations with constant coefficients by matrix methods -- Linear differential equations with variable coefficients -- Regular singular points and the method of Frobenius -- Gamma and Bessel functions -- Graphical methods for solving first-order differential equations -- Numerical methods for solving first-order differential equations -- Numerical methods for systems -- Second-order boundary-value problems -- Eigenfunction expansions -- Appendix A. Laplace transforms.
Updated edition of Schaum's outline of modern introductory differential equations. c1973.
McGraw-Hill international editions.
Includes index.
Keywords: Differential equations